Effects of time pressure on strategy selection and strategy execution in forced choice tests. Issue 5 (25th July 2019) - Orthey, Robin; Palena, Nicola; Vrij, Aldert; Meijer, Ewout; Leal, Sharon; Blank, Hartmut; Caso, Letizia
Summary: We examined the effects of cognitive load on the strategy selection in the forced choice test (FCT) when used to detect hidden crime knowledge. Examinees ( N  = 120) with and without concealed knowledge from a mock crime were subjected to an FCT either under standard circumstances or cognitive load. Cognitive load was implemented through time pressure. The FCT distinguished examinees with concealed knowledge from those without better than chance in both conditions, but the counterstrategies did not differ between conditions. Further investigation revealed that time pressure did affect examinees' ability to follow their intended counterstrategy to produce randomized test patterns, which constitutes an effective counterstrategy in the FCT. Hence, time pressure lowered the success rate of effective counterstrategies, but not their incident rates. Further disambiguation of various cognitive load manipulations and their effects on strategy selection and execution is needed.